PERSEPSI MAHASISWA TERHADAP KOMPETENSI TUTOR PADA UPBJJ UT SURAKARTA - Isman Suharto; Yulia Budiwati; Muhrom Ali Rozai (Faktor : Jurnal Ilmiah Kependidikan, 2023)
The purpose of the study was to determine the competence of tutors consisting of pedagogic competence, professional competence, personality competence and social competence in the learning process based on the perceptions of Open University students at Pokjar Grobogan. The design/methodology of this research is UPBJJ UT Surakarta students who conduct face-to-face learning by evaluating the competence of tutors, exploring questionnaires as a method of data collection. The analysis used is qualitative analysis with descriptive analysis to prove the competence of the tutor is good. Data processing is done by using percentages. The findings in this evaluation were found that students' perceptions related to tutor competence which consisted of pedagogic competence, professional competence, personality competence and social competence, in general at Pokjar Grobogan it was good. results will risk biasing the results. This study uses a research instrument adopted from a regulatory questionnaire, so that it is possible to find some weaknesses. Research development using the direct interview method in order to reduce weaknesses related to internal validity and expand the research object so that the results can be generalized